VD_FINDINFO HC / 2011 / 192 vom 14. April 2011 - VD Tribunal cantonal (2011)
MESURE PROVISIONNELLE, DIVORCE, OBLIGATION D'ENTRETIEN, REVENU HYPOTHÉTIQUE | 125 al. 1 CC, 137 al. 2 CC, 176 CC, 310 CPC (CH), 317 al. 1 CPC (CH)